The Recommendation Effect in the Hotelling Game - A New Result for an Old Model - Maximilian Conze; Michael Kramm (University of Bonn, Bonn Graduate School of Economics (BGSE), 2013)
Hotelling's famous `Principle of Minimum Differentiation' asserts that two firms engaging in spatial competition with fixed prices will decide to locate at the same place. Interpreting spatial competition as modeling product differentiation, firms will thus offer products that are not differentiated and equally share the market demand. We extend (a fixed price version of) Hotelling's model by introducing sequential consumer purchases and a second dimension of variation of the goods, quality. Consumers have differential information about the qualities of the goods and uninformed consumers observe the decision of their predecessors. With this extension a rationale for differentiating products emerges: Differentiation makes later consumers' inference from earlier consumers' purchases more informative, so that firms are confronted with two offsetting effects. On the one hand, differentiating one's product decreases the likelihood that it is bought in earlier periods, but on the other hand, by making inference more valuable, it increases the likelihood that later consumers buy the differentiated good. We show that the second effect, the recommendation effect, can dominate, leading to an equilibrium with differentiated products. Our model thus introduces an aspect similar to the herding literature in that consumers might base their decisions on observable actions of others and thus potentially on `wrong' decisions.
Keywords: L13; L15; D83; 330; Hotelling; Herding; Principle of Minimum Differentiation; Consumer Learning